Model Pendampingan Penyelenggaraan Kelompok Bermain Holistik & Integratif - Travelancya, Terza; Asfahani, Asfahani (Absorbent Mind, 2022)
Holistic and integrative early childhood education began to be discoursed by the government at the end of 2008. All types of stimulation for children and related agencies that have been developing and fostering PAUD institutions will be managed in a complete system of administrators. Various visible influences include: if the parenting pattern applied by parents to their children is not appropriate, it will undoubtedly affect their development. The purpose of this study was to determine the model for assisting the implementation of holistic and integrative play groups. The research method used is a qualitative descriptive approach. The research subject is 1 (one) person as a manager because the manager in the Mutiara Learning Group is only one person, 2 (two) tutors because the chosen one is a teacher who holds children aged between 2 - 3 years and 5 (five) parents chosen guardian. The results of the research area in implementing holistic and integrative playgroups, the services provided to children are more comprehensive and involve various parties or authorized institutions. The institutions, managers, educators, and parents have a vital role. The Play Group process in AUD (early childhood) socialization activities is a forum. Its managers and educators have carried out their tasks well by spreading learning methods similar to methods outside of school, learning with nature, and using technology or media methods.